Photocatalytic Degradation of Congo Red Textile Dye in Aqueous Solution Using TiO₂ Suspension - Patrick Okafor James Ogbunude; Jaime Souza; Alla Khanenko (Journal of Chemical Learning Innovation, 2025)
Purpose of the study: This study aims to investigate the photocatalytic degradation of Congo Red dye using TiO₂ suspension. It focuses on evaluating the effect of process conditions on degradation efficiency, examining the reaction kinetics of photodegradation, and analyzing the degradation behavior of Congo Red in aqueous solution. Methodology: Photocatalytic experiments were conducted using TiO₂ catalyst suspension and Congo Red solution. UV-C lamp (36 W) was used as radiation source in a photocatalytic reactor. Absorbance was measured using a UV–Vis spectrophotometer at 499 nm. COD was determined by closed reflux titrimetric method using K₂Cr₂O₇, Ag₂SO₄, H₂SO₄, FAS, and ferroin indicator. Mixing employed a magnetic stirrer and pH meter. Main Findings: TiO₂ photocatalysis successfully degraded Congo Red dye under UV irradiation. The optimum catalyst amount was 4.5 mg TiO₂ and the optimum irradiation time was 150 minutes. Under these conditions, degradation efficiency of Congo Red (20 ppm) reached 48.90%. COD reduction reached 84.1%, indicating significant removal of organic compounds. Increasing dye concentration decreased degradation efficiency due to higher pollutant load in the system. Novelty/Originality of this study: This study provides a systematic evaluation of photocatalytic degradation of Congo Red using TiO₂ suspension by analyzing the effects of catalyst amount, irradiation time, and dye concentration. It integrates absorbance and COD analyses to evaluate degradation efficiency, offering a clearer understanding of photocatalytic performance for textile dye wastewater treatment.